Profile of Non-Diabetic patients with Microalbuminuria in Acute Coronary Syndrome: A hospital based study - Paudel, Navaraj; Maskey, Abhishek; Karki, Dipesh; Katwal, Sushant; Thapa, Namrata (Nepalese Heart Journal, 2019)
Background and Aims: Microalbuminuria (MA) (urinary albumin excretion of 30-299 mg/d in a 24 hours collection or 30-299 μg/mg creatinine in a spot collection) is well accepted marker of micro and macrovascular damage in patients with diabetes mellitus and is considered as a surrogate marker for endothelial dysfunction in diabetic and non-diabetic patients. This study has been undertaken to investigate the prevalence of microalbuminuria among non-diabetic Acute Coronary Syndrome (ACS) patients. Methods: A hospital based cross-sectional study of 100 consecutive non-diabetic ACS patients was done. Traditional risk factors (like smoking, hypertension, dyslipidemia, obesity) of coronary artery disease were studied for the association with microalbuminuria in study subjects. Investigations were carried out in all the cases as per proforma and entered in the SPSS software for analysis. Results: The prevalence of microalbuminuria in non-diabetic ACS patients in the study was 73% which was statistically significant (p=0.04). A statistically significant higher prevalence of microalbuminuria was seen with different presentations of ACS; being highest (81.96%) in NSTEMI followed by STEMI (63.15%) and Unstable Angina (55%). It was found to be significant with the history of smoking (81.25%, p=0.013) and hypertension (82.25%, p=0.013). No significant association was found with age, body mass index (BMI) and dyslipidemia. A statistically significant higher prevalence of microalbuminuria was seen with increasing number of risk factors. Conclusion: There is increased prevalence of microalbuminuria in ACS patents. MA was associated with statistically higher number of cases with history of smoking and hypertension and presence of increasing number of risk factors.